Effects of Perinatal Antibiotic Exposure and Neonatal Gut Microbiota - Chiara Morreale; Cristina Giaroni; Andreina Baj; Laura Folgori; Lucia Barcellini; Amraj Dhami; Massimo Agosti; Ilia Bresesti (MDPI AG, 2023)
Antibiotic therapy is one of the most important strategies to treat bacterial infections. The overuse of antibiotics, especially in the perinatal period, is associated with long-lasting negative consequences such as the spread of antibiotic resistance and alterations in the composition and function of the gut microbiota, both of which negatively affect human health. In this review, we summarize recent evidence about the influence of antibiotic treatment on the neonatal gut microbiota and the subsequent negative effects on the health of the infant. We also analyze the possible microbiome-based approaches for the re-establishment of healthy microbiota in neonates.